PERJANJIAN DENGAN JAMINAN FIDUSIA BERDASARKAN PERATURAN MENTERI KEUANGAN REPUBLIK INDONESIA NOMOR 130/PMK.010/2012 - Harniwati Harniwati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The provision of fiduciary guarantees in banking transactions generally uses a notarial deed and has been clearly regulated, but how about the implementation of the fiduciary guarantee. Implementation of the Agreement with Fiduciary Guarantee Based on the Regulation of the Minister of Finance of the Republic of Indonesia Number 130/Pmk.010/2012”. The research method used in this research is mainly library research by examining secondary data, sourced from primary, secondary and research legal materials. This is done to obtain the necessary accurate data related to the problem under study. The registration of fiduciary guarantees has been determined by the Fiduciary Guarantee Law Number 42 of 1999, which is also confirmed in the Regulation of the Minister of Finance of the Republic of Indonesia Number 130/PMK.010/2012.